Impact of Community Service Activities on the Soft Skills Development of Polytechnic Engineering Students Sultan Mizan Zainal Abidin - Masfizaizan Binti Manaf; Emilawati Binti Othman; Noorashikin Binti Ahmad (Jurnal Konseling dan Pendidikan, 2018)
Community service activities are one of the activities most recently announced by all communities, government and private institutions as well as higher education centers. This activity has a positive impact on all societies, individuals and students involved in their success. Among the significant impacts of the students involved in this activity is to enhance the generic skills development of the team in terms of teamwork and problem solving skills in any field. In this study, the data were collected using a questionnaire distributed to 217 Electrical Engineering students from two to four semester at Sultan Mizan Zainal Abidin Polytechnic (PSMZA) to obtain information about the impact of teamwork and problem solving skills. The raw data obtained was processed using the SPSS version 23 software and used the Likert scale 4 for each question chosen. Data analysis showed that the mean value of the impact of community service activities on teamwork skills was 3.26 and problem solving skills (3.68) where it was stand in high level for two to four semester electrical engineering students. The results of the t-test experiments found that there was no significant difference between male and female students on the impact of community activities on the components of teamwork skills where p> 0.05 and there is little difference between male and female students for problem solving skills where p <0.05. It is thus envisaged that this community service activity is crucial to be applied to all polytechnic students as a condition of awarding diploma and in line with the requirement of the National Education Philosophy to produce individuals who are intellectually, spiritually, emotionally and physically balanced.